'A Vast Surface of Brains': Machado de Assis and Stupid Reading. (1st April 2019) - Penteado, Bruno
Abstract: In this essay I offer an analysis of Machado de Assis's 1882 novella O Alienista in which I question the transposition of metropolitan reading practices to a colonial setting. After an introduction to nineteenth-century French alienism, a tradition that was adopted in Brazil when the first insane asylum opened in Rio during the reign of Pedro II, I move on to read the very reading practices of an alienist responsible for committing four-fifths of the population of a small town to the recently established Green House. Suggesting that, in his radical rationality, the alienist fails to read idiocy as idiosyncrasy, I argue that his reading of the mental faculties of others embodies the stupidity both of the pursuit of literality/universality and of the mimicking of European thought without turning such mimicry into mockery. Borrowing the concept of 'misplaced ideas' from theorist Roberto Schwarz while also alluding to the alienist's inability to mock as he mimics (as theorized by Homi Bhabha), I contend that Bacamarte's failure to see that European ideas and doctrines are misplaced/out of place in Brazil turns his reading of alienation into an utterly stupid practice.